Betamethasone versus dexamethasone for inpatient preschool wheezing—A case‐control study. Issue 5 (1st February 2021) - Gileles‐Hillel, Alex; Guttman, Sharon; Breuer, Oded; Reiter, Joel; Leshem, Regina; Shoseyov, David; Kerem, Eitan; Cohen‐Cymberknoh, Malena
Abstract: Background and Objectives: Wheezing is one of the most common reasons for the presentation of children to primary care or the emergency ward, before 7 years of age. Current guidelines recommend a short course of oral corticosteroids (OCS) for those children with a wheezing attack severe enough to require hospitalization. However, the optimal choice of therapy is controversial. We aimed to compare the efficacy of betamethasone to that of dexamethasone in achieving clinical response in preschool children requiring hospitalization for an acute wheezing attack. Methods: This was a retrospective study. Medical records of healthy children without significant comorbidities between 1 and 7 years of age ( n  = 234) admitted with a moderate‐severity acute wheezing attack to two pediatric wards between 2014 and 2018 were included. All children were treated with either betamethasone or dexamethasone exclusively during the hospitalization. The primary outcome of interest was the length of hospital stay (LOS). Results: The demographic parameters and the clinical severity of wheezing episodes were similar in the two study groups, as was the LOS. However, the dexamethasone cumulative dose used during hospitalization was significantly larger than the betamethasone cumulative dose (3.76 (1.88–5.64) vs. 1.86 (1.24–3.1) mg/kg of prednisone‐equivalent dose, p  < .001). Conclusion: In preschool children with acute wheezing requiring hospitalization, betamethasone achieved a similar clinical response when compared to dexamethasone, with a lower cumulative steroid dose. Further studies are needed to understand the additional benefits of betamethasone over other steroids or placebo.